A Collaborative Approach to School Community Engagement with a Local CCS Project. (July 2017) - Bloxsome, Belinda; Van Gent, Dominique; Stalker, Linda; Ferguson, Beth
Abstract: The future of Carbon Capture and Storage (CCS) deployment requires research on geological, technical, economic, community and educational fronts. A program that has been running since 2009, CSIRO's Sustainable Futures – CarbonKids, is an education program that combines the latest in climate science with education for sustainability, with a strong focus on carbon. In 2012 the Global Carbon Capture and Storage Institute (GCCSI) funded the CSIRO to develop and deliver 'carbon capture and storage' educational materials to be embedded into wider sustainability educational resources under the banner of CarbonKids, now Sustainable Futures - CarbonKids. Resources include a wealth of cross-curricular activities to support the teaching of sustainability and the environment in the classroom, school and community. The Western Australian Department of Mines and Petroleum (WA DMP) is conducting the pre-feasibility phase of the South West Hub CCS Project (SW Hub) in the South West region of Western Australia. CSIRO Sustainable Futures – CarbonKids program partnered with WA DMP in 2013 to implement an innovative and unique approach to educating teachers, students and the community in the science and understanding of the carbon cycle and CCS. This partnership provides schools registered with Sustainable Futures – CarbonKids a suite of educational resources including carbon and CCS activities. Access to the program also provides opportunities for teachers and students to meet and learn from representatives of WA DMP, and research scientists from WA DMP's research partner the National Geosequestration Laboratory (NGL), who work collaboratively on the SW Hub. This brings real life science into the classroom; providing students and teachers with examples of local scientific knowledge being used to solve problems and enhancing their understanding of the effects of their personal actions relating to energy and carbon, which is an important learning requirement within school curricula. The aim of the collaboration with the SW Hub is to provide information and the opportunity for learning from a real world case (the SW Hub CCS project) which will increase awareness of carbon and the environment in schools, and improve students' understanding of activities relating to carbon, energy and low carbon technology CCS research.